The pragmatic function of asides that stage an event in the Fourth Gospel - R.S. Hobyane (Acta Theologica)
This article seeks to investigate how asides that function to stage an event in the Fourth Gospel fulfil their pragmatic/performative role. Despite numerous insightful contributions on this topic, the article contends that scholars have not comprehensively explored this specific literary device in the Fourth Gospel. It therefore seeks to contribute to Johannine research by analysing these specific asides from a speech act interpretive perspective. It aims to demonstrate that these asides are inherently performative, representing a deliberate communicative strategy by the implied author to engage and compel participation from the reader. The article concludes that asides that function to stage an event play a performativerole and contribute to enhancing the attainability of the overall purpose of the Gospel (20:30-31).